2022
DOI: 10.3390/pharmaceutics14102088
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Peptide Chm-273s Has Therapeutic Potential for Metabolic Disorders: Evidence from In Vitro Studies and High-Sucrose Diet and High-Fat Diet Rodent Models

Abstract: The aim of this study was to develop a novel peptide potentially applicable for the treatment of metabolic conditions, such as obesity and type 2 diabetes (T2D). We identified CHM-273S from the list of peptides from milk hydrolysate obtained by HPLC/MS-MS. In vitro analysis of primary murine fibroblasts indicated the potential of CHM-273S to upregulate IRS2 mRNA expression. CHM-273S showed a prominent anorexigenic effect in mice with the induction of a key mechanism of leptin signaling via STAT3 in the hypotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Here we employed computational modeling to search for peptides that interact with the NAM site of mGluR5. We focused on peptides as potential therapeutics because of their safety and tolerability profiles, which are superior to those of other small molecules ( Lau and Dunn, 2018 ; Malyshev et al, 2021 ; Mitkin et al, 2022 ). We identified four novel, previously undescribed peptides with predicted affinity to the mGluR5 NAM site based on in silico docking studies and revealed that two of them, LCGM-10 and LCGM-15, have a potential stimulating effect in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…Here we employed computational modeling to search for peptides that interact with the NAM site of mGluR5. We focused on peptides as potential therapeutics because of their safety and tolerability profiles, which are superior to those of other small molecules ( Lau and Dunn, 2018 ; Malyshev et al, 2021 ; Mitkin et al, 2022 ). We identified four novel, previously undescribed peptides with predicted affinity to the mGluR5 NAM site based on in silico docking studies and revealed that two of them, LCGM-10 and LCGM-15, have a potential stimulating effect in zebrafish.…”
Section: Introductionmentioning
confidence: 99%